Generation of dual-wavelength ytterbium-doped fibre laser using a highly nonlinear fibre - Salim, Muhammad Aizi Mat; Azzuhri, Saaidal Razalli; Abdul Khudus, Muhammad Imran Mustafa; Razak, Mohd Zulhakimi Ab; Nasir, N.S.; Amiri, Iraj Sadegh (IOP Publishing, 2018)
This paper describes the dual-wavelength operation in the 1060 nm region by applying an ytterbium-doped gain medium fiber and a highly nonlinear fiber (HNLF) as the wavelength selective filter. Due to its nonlinear properties and birefringence co-efficient, the HNLF also functions as a stabilizer for dual-wavelength fiber laser operation. Results from the experiment show that the fluctuated power of the system is less than 0.6 dB when continuously run for 20 min, indicating the system's stability. The spacing of the dual-wavelength output is obtained by fine-tuning the polarization controller within the fiber ring laser setup. The spacing ranges between 2.7 nm-21.05 nm.